Utilization of water hyacinth plants as a woven craft business opportunity in subdistrict 1 Ilir Palembang city - Citra Iasha; Dian Novita Fajar Sari; Andela Anggleni; Deffi Haryani (Abdimas Paspama, 2024)
The reason for community service is because many water hyacinth plants grow massively and fertilely and are underutilized, so assistance is needed so that these plants have added value for the community, especially increasing income. One of the locations where water hyacinth grows in abundance is in the Air area, 1 Ilir Village, Ilir Timur II District, Palembang City, South Sumatra. In this activity, it was introduced that the water hyacinth plant is made into a woven craft which is useful as a business opportunity as an alternative to increasing income. . Methods used Training. and discussion and diffusion of water hyacinth fiber processing technology. The processing processes are: process, making patterns, weaving process, embroidery process, making handles, sewing, finishing. In conclusion, with community service, water hyacinth training can reduce the negative impact of the presence of water hyacinth which can reduce oxygen levels in the water. As well as empowering local communities who are tasked with weaving these crafts. Apart from that, the marketing scope is also getting wider as evidenced by the presence of orders for water hyacinth crafts not only from within the city but from outside the city and even overseas.